Sex Hormones in Neurodegenerative Processes and Diseases - Drevenšek, Gorazd (IntechOpen, 2018)
The book provides chapters on sex hormones and their modulation in neurodegenerative processes and pathologies, from basic molecular mechanisms, physiology, gender differences, to neuroprotection and clinical aspects for potential novel pharmacotherapy approaches. The book contains 14 chapters written by authors from various biomedical professions, from basic researchers in biology and physiology to medicine and veterinary medicine, pharmacologists, psychiatrist, etc. Chapters sum up the past and current knowledge on sex hormones, representing original new insights into their role in brain functioning, mental disorders and neurodegenerative diseases. The book is written for a broad range of audience, from biomedical students to highly profiled medical specialists and biomedical researchers, helping them to expand their knowledge on sex hormones in neurodegenerative processes and opening new questions for further investigation.